Possibility of enterohepatic recycling of ketoprofen in dogs - Granero, Gladys Ester (2008)
Ketoprofen is mainly cleared by glucuronidation. The rate of glucuronidation of this compound has been demonstrated to be greater in dog than in human liver microsomes. Dog is the most common secondary nonprimate species used in drug metabolism studies in the pharmaceutical industry. Therefore, this study was undertaken to provide valuable information to pharmaceutical companies using dog as a model species for pharmacokinetic analyses when differences in glucuronidation occur across species for therapeutic drugs known to be extensively glucuronidated. The pharmacokinetics of ketoprofen was investigated after intravenous (0.27, 0.57 and 1.10 mg/kg) and oral administration of ketoprofen (∼10 mg/100 ml) of the racemate in dogs. Serial blood samples were collected at timed intervals for 7 and 24 h following intravenous and oral administration of the dose, respectively, and concentrations in plasma were determined by a sensitive and specific HPLC method. By comparing the AUC0−∞ following oral and intravenous administrations, ketoprofen bioavailability was ∼100%. A possibility of enterohepatic cycling of ketoprofen in dogs was proposed because of multiple peak phenomenon in the concentration?time profiles after intravenous and oral dosing was observed.